Antibiotic Use in Diabetes Mellitus Patients with Gangrene at Abdoel Wahab Sjahranie Samarinda Hospital (Sciences of Pharmacy, 2022)
Gangrene is one of the complications of diabetes mellitus. Along with the rising prevalence of diabetes mellitus (DM), the prevalence of gangrene and necrosis manifestations such as ulcers and infections will ascend. The selection of appropriate antibiotics is critical in infection therapy. Inappropriate use of antibiotics will result in antibiotic resistance. Therefore, this research aims to overview demographic, clinical characteristics, antibiotic use profiles, and antibiotic-related problems for DM patients with gangrene at the Abdoel Wahab Sjahranie Samarinda Hospital. The study was retrospective research and was conducted in July-December 2021. Twenty-one patients met the inclusion criteria, and demographic data showed that most patients were men 57% (n=11), and most age was 39-59 years (57%, n=12). The longest period of suffering from gangrene was 6-10 years (14%, n=3). The most common length of hospitalization was 8-14 days, as reported by 52 percent (n=11) of patients, and the most common duration of antibiotic use was ten days, as reported by 86 percent (n=18) of patients. A single-used antibiotic was ceftriaxone (19%, n=4) patients. The most used antibiotic combination was ceftriaxone and metronidazole (81%, n=17). Fourteen patients used antibiotics appropriately in dosage, route, and frequency. Four patients were unsuitable for the benefit of antibiotics in terms of antibiotic type, and three patients were unsuitable for antibiotic use in terms of duration of administration.